Multilingual Teaching Materials Based on Local Culture Theme My Family for First Grade Elementary School Students - Kaka, Pelipus Wungo; Yohanes Vianey Sayang; Ermelinda Yosefa Awe (Universitas Pendidikan Ganesha, 2024)
The absence of multilingual teaching materials does not have an impact on students' ability to understand local cultural competition material. Based on this, the aim of this research is to develop multilingual teaching materials based on the local cultural content and context of the Ngada tribe with the theme My Family which is appropriate to the characteristics of grade I elementary school students. This type of research is development research with the ADDIE model (analysis, design, development, implementation and evaluation). The data sources obtained from this research are content/material experts, Indonesian language experts, regional language experts and design experts. The data collection method uses a questionnaire. The data collection instrument uses a questionnaire sheet. The data analysis technique uses qualitative and quantitative descriptive analysis. The research results are This teaching material has the potential to be an effective innovation in supporting inclusive, contextual and meaningful early learning. The conclusion of this research states that the teaching materials developed have proven effective in increasing students' understanding of learning materials, strengthening early literacy skills, and fostering appreciation for the diversity of local languages and cultures. The integration of Indonesian, regional languages and English in one teaching material that is contextual to students' lives has been proven to be able to create more enjoyable, relevant and meaningful learning. The implications of this research indicate that developing teaching materials that combine a multilingual approach and local cultural content can be an effective strategy in improving the quality of learning in elementary schools, especially in the early grades.